An analysis of electrochemical corrosion on pipeline steel in silty soil under salt-temperature coupling environments. (15th June 2023) - Sun, Funan; Han, Pengju; He, Bin
Highlights: Dissolution rate is limited by cathodic processes in moist soil at a decreasing temperature. A method is proposed to calculate kinetic parameters and structural parameters of corrosion of metal matrix through further derivation. Combined with SEM, the surge distribution of passivation current density before and after soil freezing is revealed. In deeply frozen soil, the transition of corrosion forms on steel surfaces is revealed. Abstract: The initial corrosion evolution process of X80 steel exposed to silty soil mixed with NaCl at increasing salinities and temperatures was investigated. Based on the electrochemical testing and microscopic observations, the analysis results indicate dissolution rate is limited by cathodic processes in moist soil. The migration and accumulation of Cl − ions on the oxide film surface are driven by soil water potential after soil freezing, resulting in the decomposition of the film. The release of Fe 2+ accelerates the passivation rate. The growth of salt and ice water crystals on the steel-soil interface expands the void between the soil particles, thereby further increasing the diameter of the corrosion pit.